2005
DOI: 10.1161/01.atv.0000160613.57985.18
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated With Carotid Atherosclerosis

Abstract: Objective-Nonalcoholic fatty liver disease (NAFLD) frequently coexists with obesity, diabetes, and dyslipidemia. We examined whether NAFLD was associated with atherosclerosis, as measured by ultrasound in the carotid arteries. Methods and Results-Carotid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
238
4
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(269 citation statements)
references
References 41 publications
18
238
4
6
Order By: Relevance
“…This finding clearly indicated that subjects with a high-normal ALT might be susceptible to carotid atherosclerosis. There are many cross-sectional [13][14][15][16] and prospective [9,17,18] studies on the association between NAFLD and intermediate markers of cardiovascular disease or clinical outcomes. These studies have reported that ultrasounddiagnosed liver steatosis or raised serum concentrations of liver enzymes predict an increased risk of cardiovascular disease, independent of several established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…This finding clearly indicated that subjects with a high-normal ALT might be susceptible to carotid atherosclerosis. There are many cross-sectional [13][14][15][16] and prospective [9,17,18] studies on the association between NAFLD and intermediate markers of cardiovascular disease or clinical outcomes. These studies have reported that ultrasounddiagnosed liver steatosis or raised serum concentrations of liver enzymes predict an increased risk of cardiovascular disease, independent of several established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The main cross-sectional [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and prospective [11,[32][33][34][35][36][37][38][39][40][41][42][43] studies on the association between NAFLD and intermediate markers of CVDor clinical outcomes are shown in Tables 1 and 2 of the Electronic supplementary material. NAFLD, endothelial dysfunction, early carotid atherosclerosis and left ventricular dysfunction NAFLD is associated with circulatory endothelial dysfunction [16,17], a marker of early atherosclerosis. Compared with non-steatotic controls, non-diabetic patients with NAFLD show a significant decrease in brachial artery flow-mediated vasodilation, which is related to the severity of NAFLD histology, independently of age, sex, BMI and HOMA-IR [16].…”
Section: Evidence Linking Nafld With Cvdmentioning
confidence: 99%
“…Carotid artery intima-media thickness (IMT), another marker of early atherosclerosis, is also markedly increased in patients with NAFLD patients compared with that in age-, sex-and BMI-matched healthy controls [20][21][22][23][24][25], and NAFLD histology predicts carotid IMT independently of traditional risk factors, HOMA-IR and features of the metabolic syndrome [24]. Similarly, patients with NAFLD, also in the absence of obesity, hypertension and diabetes, exhibit echocardiographic features of early left ventricular dysfunction [18] and impaired energy metabolism as measured by cardiac 31 P magnetic resonance spectroscopy [19].…”
Section: Evidence Linking Nafld With Cvdmentioning
confidence: 99%
“…Indeed, in the last 5 years NAFLD has emerged as an independent risk factor for CVD. Several studies have observed increased carotid intima-media thickness and carotid plaques in patients with NAFLD, including children (39,(107)(108)(109)(110)(111) . Although there has been some conflicting work (112) , a systematic review has found that carotid plaques are two to three times more likely to be observed in patients with NAFLD and intima-media thickness is strongly associated with NAFLD (113) .…”
Section: Genetic and Environmental Factors Associated With Non-alcohomentioning
confidence: 99%